Dis/connected: Malaysian identity 'crisis' in Malaysian poetry in English - Abdul Manaf, Nor Faridah (De La Salle University, Manila Philippines, 2004)
This article looks at the identity "crisis" faced when writing literature in Malaysia due to it's diversity and ever changing nature.